Minimizing anticholinergic drug prescribing in older hospitalized patients: a full audit cycle. (June 2014) - Tay, Hui Sian; Soiza, Roy L; Mangoni, Arduino A
Introduction: Anticholinergic drugs are associated with poor outcomes in older patients but no specific intervention strategies aimed at reducing anticholinergic drug exposure have been described. Objectives: To identify whether a consultant-led medication review targeting anticholinergics would reduce anticholinergic drug exposure [number of anticholinergic drugs and Anticholinergic Risk Scale (ARS) score]. Methods: The first phase of the audit included 70 consecutive admissions (mean age 84 years, 53 women). ARS score was calculated on admission and after initial consultant review. Re-audit was undertaken on another 70 consecutive admissions (mean age 83 years, 43 women) after introducing a system of informing the responsible consultant of the ARS score at their first review. Results: Drugs with anticholinergic effects ( n = 53) were prescribed preadmission to 45/140 (32%) of patients. Consultant geriatrician review reduced ARS scores ( p = 0.01), especially following the introduction of the information system ( p = 0.002). In the first arm of the audit, 51 (73%) patients had ARS of 0 after a consultant's review compared with 47 (67%) patients on admission, whilst 67 (96%) patients had ARS of 2 or less after a consultant's review compared with 63 (90%) patients on admission. In the second arm of the audit, 59 (84%) patients had ARS of 0 after a consultant's review compared with 48 (69%) patients on admission, whilst 70 (100%) patients had ARS of 2 or less after a consultant's review compared with 69 (99%) patients on admission. Anticholinergic drugs were either stopped, or their dose reduced, in 35% of patients in the first arm of the audit and in 73% of patients in the re-audit (odds ratio 5.0, 95% confidence interval 1.4–17.8). Conclusion: Consultant-led medication review (standard practice) was effective at reducing anticholinergic drug exposure in the acute setting. A system of alerting clinicians to patients prescribed anticholinergic medications further reduced anticholinergic drug exposure.